KREASI PENGOLAHAN ABON JANTUNG PISANG - ., Aisyah (LPPM Universitas PGRI Adi Buana Surabaya, 2017)
Basically, banana inflorescence is a part of banana trees that useless. Despite it's cheap price the banana inflorescence have benefits as a healthier food ingredients due to the high fiber and low fat content. The texture of abon also good for elder people and children. The purpose of this study is to invite people to utilize banana inflorescence as a high protein food ingredient.